Methods of chaotic dynamics in schemes of researches feasibility internals of car traffic volumes - Kramarenko, H. A.; Nechay, A. V.; Skalozub, V. V. (Science and Transport Progress, 2011)
The possibilities of chaotic dynamics methods applied to the topical analysis and forecasting problems of economic and technological properties of wagon streams represented by the related time series are studied. The advisability of using the generalized logistic map method for the construction of time series behavior operational forecasting is also determined.